2020
DOI: 10.1002/jocb.439
|View full text |Cite
|
Sign up to set email alerts
|

Does Cognitive Style Moderate Expected Evaluation and Adolescents' Creative Performance: An Empirical Study

Abstract: Two studies investigated the effects of cognitive and school environmental factors on adolescents' creative performance. The first study tested the effects of expected evaluation and cognitive style on creativity among 89 high school students. The second study tested the effects of evaluation type and cognitive style on creativity among 92 high school students. Study 1 found main effects of expected evaluation and cognitive style on creativity. The interaction between expected evaluation and cognitive style wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 34 publications
(59 reference statements)
1
14
0
Order By: Relevance
“…This result was also confirmed by the ANOVA, showing that FIs provided significantly higher scores in originality and appropriateness than FDs, meaning that the faster participants were in identifying the simple shape embedded in the complex figure (field independence), the more creative (original and appropriate) were their inventions. Results confirmed H2 and align with previous studies on real-world creative production [ 29 , 39 ] as well as research on both divergent thinking [ 17 , 19 , 32 ] and convergent thinking [ 36 , 37 ]. Two main explanations can explain the better performance of FIs in the VCST than FDs.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…This result was also confirmed by the ANOVA, showing that FIs provided significantly higher scores in originality and appropriateness than FDs, meaning that the faster participants were in identifying the simple shape embedded in the complex figure (field independence), the more creative (original and appropriate) were their inventions. Results confirmed H2 and align with previous studies on real-world creative production [ 29 , 39 ] as well as research on both divergent thinking [ 17 , 19 , 32 ] and convergent thinking [ 36 , 37 ]. Two main explanations can explain the better performance of FIs in the VCST than FDs.…”
Section: Discussionsupporting
confidence: 89%
“…Given the multifaceted nature of creativity, the impact of cognitive factors on creative accomplishment has been long discussed in the past [ 16 ]. Cognitive style, also known as thinking style, represents a pivotal factor unquestionably related to creativity [ 17 ]. The expression cognitive style refers to how people acquire, organize, and use information [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…All the eight articles selected for this systematic review hypothesized a relation between FDI and creativity, and they were published from 1967 to 2020. Of the eight articles, four employed a between study design (Lei et al, 2021;Li et al, 2020;Miller, 2007;Saracho, 1992), three a correlational study design (Baranovská et al, 2017;Fergusson, 1992Fergusson, , 1993Saurenman & Michael, 1980), and one used both between and correlational research designs (Noppe & Gallagher, 1977).…”
Section: Study Design and Sample Characteristicsmentioning
confidence: 99%
“…One study (Spotts & Mackler, 1967) indicated that the sample was composed of undergraduate students and one study (Noppe & Gallagher, 1977) of education majors. In addition, one study reported only the percentage of gender (Lei et al, 2021). Only one study involved children (Saracho, 1992), one pre-adolescent (Saurenman & Michael, 1980), two adolescents (Baranovská et al, 2017;Lei et al, 2021), three young adults (Miller, 2007;Noppe & Gallagher, 1977;Spotts & Mackler, 1967), whereas one study focused on both adolescents and young adults (Li et al, 2020).…”
Section: End Of Tablementioning
confidence: 99%